2016
DOI: 10.1016/j.bbabio.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

cAMP regulates the functional activity, coupling efficiency and structural organization of mammalian F O F 1 ATP synthase

Abstract: The present study shows that in isolated mitochondria and myoblast cultures depletion of cAMP, induced by sAC inhibition, depresses both ATP synthesis and hydrolysis by the FOF1 ATP synthase (complex V) of the oxidative phosphorylation system (OXPHOS). These effects are accompanied by the decrease of the respiratory membrane potential, decreased level of FOF1 connecting subunits and depressed oligomerization of the complex. All these effects of sAC inhibition are prevented by the addition of the membrane-perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Similarly, mitochondrial PKA can modulate complex V activity. Local PKA phosphorylation of ATPase inhibitory factor 1 (AIF1) on Ser39 prevents the interaction between AIF1 and complex V maintaining ATP synthase activity . Also, decreasing PKA activity in mitochondria can lead to the proteolytic degradation of complex V components resulting in less ATP synthesis .…”
Section: Protein Kinase a G C (Agc Kinases)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mitochondrial PKA can modulate complex V activity. Local PKA phosphorylation of ATPase inhibitory factor 1 (AIF1) on Ser39 prevents the interaction between AIF1 and complex V maintaining ATP synthase activity . Also, decreasing PKA activity in mitochondria can lead to the proteolytic degradation of complex V components resulting in less ATP synthesis .…”
Section: Protein Kinase a G C (Agc Kinases)mentioning
confidence: 99%
“…117,118 Also, decreasing PKA activity in mitochondria can lead to the proteolytic degradation of complex V components resulting in less ATP synthesis. 118,119 The proximity of PKA to the bioenergetic machinery makes the kinase a useful regulator of ATP production and the ETC Furthermore, the relationship between ATP production and mitochondrial PKA activity extends to the PKA phosphorylation of TOM22 can also impair its transport functions. 124 Similarly, PKA can phosphorylate TOM70 on Ser174, which inhibits TOM70 receptor-type activities toward chaperone functions such as Hsp70.…”
Section: Pka Phosphorylation Of Drp-1 On Ser637 Impairs the Function Ofmentioning
confidence: 99%
“…It has been reported that F-ATPase/ATP synthase retains the hydrolytic and synthase activities in isolated mitochondria [21]. Further, it is known that under the right storage conditions, the mitochondrial ATPase has been shown to remain active for weeks after isolation [22].…”
Section: Resultsmentioning
confidence: 99%
“…Given that CO 2 is the end product of the TCA cycle, the cAMP-PKA pathway provides a feed-forward regulation on two modules of energy metabolism: TCA cycle and ETC complexes. Recently, Complex V activity has also been found under the regulation of matrix cAMP-PKA pathway [123125]. Complex V (mitochondrial ATP synthase) catalyzes the synthesis of ATP through the proton gradient generated by the ETC complexes and executes the reverse hydrolysis when the membrane potential falls below a threshold (pH of ~6.7 or below) [126].…”
Section: Camp Signaling Inside the Matrix (Fig 3)mentioning
confidence: 99%
“…Thus the phosphorylation status of IF1 appears to be key in regulating the flux of glycolysis and OXPHOS corresponding to certain physiological context [124]. Furthermore, De Rasmo and colleagues recently have demonstrated the importance of the sAC-cAMP signaling for the organization and activity of Complex V in isolated rat mitochondria and myoblast cultures [125]. …”
Section: Camp Signaling Inside the Matrix (Fig 3)mentioning
confidence: 99%